Phase behaviour of alkynyl-terminated bicyclo[3.3.0]octa-1, 4-diene ligands: a serendipitous discovery of novel calamitic liquid crystals. Issue 11 (2nd September 2021) - Schulz, Finn; Deimling, Max; Laschat, Sabine
ABSTRACT: Chiral bicyclo[3.3.0]octadienes carrying two alkoxy- or alkynyloxy side chains are highly valuable ligands for asymmetric catalysis but have never been explored regarding their liquid crystalline self-assembly. Therefore, a series of bicyclo[3.3.0]octadienes was synthesised and studied by differential scanning calorimetry (DSC), polarising optical microscopy (POM) and X-ray diffraction (XRD) to understand the role of the terminal alkyne unit in the side chain. Dienes with hexinyloxy or octinyloxy side chains behaved similar to the diene with hexyloxy chains, showing broad SmA phases and a pronounced tendency for supercooling. In contrast, dienes with mono- or diethylenglycolpropargylic ether chains displayed a decreased phase range and monotropic behaviour in the latter case, while the corresponding diene with propargylether side chains was non-mesomorphic. Graphical abstract: uf0001